Comparative analysis of critical literacy in lower secondary curricula in Finland, Italy and Spain: implications for CLIL - Bozbiyik, Merve; Tompkins, Leah; Morton, Tom; Gerns, Pilar; Kääntä, Leila; Sulkunen, Sari; Pérez-Fernández, Lucila (Journal of Multilingual and Multicultural Development, 2026)
Critical literacy (CL), which refers to the use of diverse communication media to analyse and critique everyday social practices, has often been credited with advancing inclusion and diversity in schools. However, criticality has been seen as a missing dimension in Content and Language Integrated Learning (CLIL), and the extent to which it figures in mainstream curricular documents is unclear. In this scenario, we aim to determine how CL is represented in lower secondary curricula in different national contexts and subject areas. We examined curricula in history and biology subjects, which are commonly taught through a CLIL approach, in three national contexts: Finland, Italy, and Spain. We used a combination of bottom-up and top-down approaches, complementing an analysis of curriculum documents with a coding process informed by CL and Critical Thinking (CT) theories. The study reveals that CT and CL are present in both biology and history, but are emphasised differently across countries. Biology curricula tend to integrate CL more visibly, while history favours CT despite its disciplinary potential for perspective-taking. These differences highlight the need for greater balance and explicitness in how criticality is represented across subjects, with implications for designing curricula that better support criticality, both in mainstream and CLIL contexts.
Keywords: critical literacy; disciplinary literacy; CLIL; lower secondary education; curriculum analysis